(untitled) (Nonlinear Studies, 2014)
This paper unifies the results on stability, controllability and observability criteria on realÂ time dynamical systems and deduce the results on continuous/discrete systems as a particular case. We further study the stability analysis of real time dynamical system on Measure chains in one dimensionalÂ state space ΔÂ systems.